Analysis of clinical factors and inflammatory cytokines in patients with lung cancer and sarcopenia: a prospective single-center cohort study - Liu, Yalan; Zhang, Hui; Chen, Peng; Liu, Xinfu (Frontiers in Oncology, 2025)
ObjectiveTo analyze the relationship between the expression of various clinical factors, inflammatory cytokines, and sarcopenia and provide new ideas for whole-course management and curative effect prediction in patients with lung cancer and sarcopenia.MethodsA total of 135 patients with lung cancer recruited in the Department of Oncology, Central Hospital of Shaoyang, from January 2022 to January 2024 were analyzed and divided into sarcopenia (75 cases) and non-sarcopenia (60 cases) groups. Various statistical analyses methods were used to analyze the correlation between 4 kinds of inflammatory cytokines and sarcopenia in patients with lung cancer.ResultsIn this study, 55.6% (75/135) of the lung cancer patients were found to have sarcopenia, with a median age of 67.3 years. Those with sarcopenia were found to be significantly associated with increased age, long duration of cigarette inhalation, and high risk of malnutrition. The results of the regression analysis indicated that long-term cigarette inhalation (odds ratio [OR]=8.187), body mass index (BMI; OR=1.356), and Nutritional Risk Screening 2002 score (OR=0.050) were statistically significant (P<0.05). Multivariable logistic regression analysis indicated that patients in the sarcopenia group were positively correlated with interleukin (IL)-6 and tumour necrosis factor (TNF)-α (P<0.05). The progression-free and overall survival of lung cancer patients with sarcopenia who received chemotherapy were significantly increased compared to those who did not receive chemotherapy(P<0.05).ConclusionsPatients with a long-term cigarette inhalation, high risk of malnutrition, and low BMI have a higher probability of sarcopenia. The increased expression levels of IL-6 are positively correlated with the occurrence of sarcopenia, as well as TNF-α. The intervention of chemotherapy affects inflammatory cytokine levels. Early chemotherapy may extend the survival time of patients with lung cancer and sarcopenia.